Acrolein and Copper as Competitive Effectors of α‐Synuclein. Issue 8 (28th January 2020) - Falcone, Enrico; Ahmed, Ikhlas M. M.; Oliveri, Valentina; Bellia, Francesco; Vileno, Bertrand; El Khoury, Youssef; Hellwig, Petra; Faller, Peter; Vecchio, Graziella
Abstract: Mounting evidence supports the role of amyloidogenesis, oxidative stress, and metal dyshomeostasis in the development of neurodegenerative disorders. Parkinson's Disease is characterized by α‐synuclein (αSyn) accumulation and aggregation in brain regions, also promoted by Cu 2+ . αSyn is modified by reactive carbonyl species, including acrolein (ACR). Notwithstanding these findings, the interplay between ACR, copper, and αSyn has never been investigated. Therefore, we explored more thoroughly the effects of ACR on αSyn using an approach based on LC‐MS/MS analysis. We also evaluated the influence of Cu 2+ on the protein carbonylation and how the ACR modification impacts the Cu 2+ binding and the production of Reactive Oxygen Species (ROS). Finally, we investigated the effects of ACR and Cu 2+ ions on the αSyn aggregation by dynamic light scattering and fluorescence assays. Cu 2+ regioselectively inhibits the modification of His50 by ACR, the carbonylation lowers the affinity of His50 for Cu 2+ and ACR inhibits αSyn aggregation both in the presence and in the absence of Cu 2+ . Abstract : Acting together? Copper(II) and acrolein compete for the same target residue of α‐synuclein. The combined effects of the metal coordination and the carbonylation play an important role on the α‐synuclein aggregation, thus potentially affecting the onset and progression of Parkinson's disease.